Metastatic Uterine Leiomyosarcoma in the Upper Buccal Gingiva Misdiagnosed as an Epulis. (15th October 2014) - Cassoni, Andrea; Terenzi, Valentina; Bartoli, Davina; Rajabtork Zadeh, Oriana; Battisti, Andrea; Pagnoni, Mario; Conte, Davide; Lembo, Alessandro; Bosco, Sandro; Alesini, Francesco; Valentini, Valentino
Abstract : Uterine leiomyosarcoma (LMS) is a rare tumor constituting 1% of all uterine malignancies. This sarcoma demonstrates an aggressive growth pattern with an high rate of recurrence with hematologic dissemination; the most common sites are lung, liver, and peritoneal cavity, head and neck district being rarely interested. Only other four cases of metastasis in the oral cavity have been previously described. The treatment of choice is surgery and the use of adjuvant chemotherapy and radiation has limited impact on clinical outcome. In case of metastases, surgical excision can be performed considering extent of disease, number and type of distant lesions, disease free interval from the initial diagnosis to the time of metastases, and expected life span. We illustrate a case of uterine LMS metastasis in the upper buccal gingiva that occurred during chemotherapy in a 63-year-old woman that underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy for a diagnosis of LMS staged as pT2bN0 and that developed lung metastases eight months after primary treatment. Surgical excision of the oral mass (previously misdiagnosed as epulis at a dental center) and contemporary reconstruction with pedicled temporalis muscle flap was performed in order to improve quality of life. Even if resection was achieved in free margins, "local" relapse was observed 5 months after surgery.